(untitled) (Research, Society and Development, 2022)
Objective: To describe the epidemiological profile of deaths from traffic accidents in the state of Pernambuco from 2015 to 2019. Methods: This is a cross-sectional, descriptive research with quantitative approach, from which case notifications were collected of traffic accidents in the state of Pernambuco, from the records of the Mortality Information System notification forms from 2015 to 2019. The results were organized by year of notification, analyzing the following variables: age group, color/race, education, marital status, place of death and sex. Results: In the analyzed period, 8,572 deaths were recorded, the year 2015 marked the highest rate of deaths. Individuals aged 20 to 29 years (23.9%), brown color/race (79.1%), men (85.3%), 4 to 7 years of schooling (28.1%) and individuals singles (59%) were the most affected. The fatalities of traffic accidents still took place on public roads (52.2%). Conclusion: It is concluded that young people were the ones who died the most. Scientific evidence from an epidemiological profile is crucial for strengthening existing public policies and/or creating new resources that end or minimize such imbroglios.